Advancing fence datasets: Comparing approaches to map fence locations and specifications in southwest Montana - Buzzard, Simon A.; Jakes, Andrew F.; Pearson, Amy J.; Broberg, Len (Frontiers in Conservation Science, 2022)
Fencing is a major anthropogenic feature affecting wildlife distributions and movements but its impacts are difficult to quantify due to a widespread lack of spatial data. We created a fence model and compared outputs to a fence mapping approach using satellite imagery in two counties in southwest Montana, USA to advance fence data development for use in research and management. The model incorporated road, land cover, ownership, and grazing boundary spatial layers to predict fence locations. We validated the model using data collected on randomized road transects (n = 330). The model predicted ~34,700 km of fences with a mean fence density of 0.93 km/km2 and a maximum density of 14.9 km/km2. We also digitized fences using Google Earth Pro in a random subset of our study area in survey townships (n = 50). The Google Earth approach showed greater agreement (K = 0.76) with known samples than the fence model (K = 0.56) yet was unable to map fences in forests and was significantly more time intensive. We also compared fence attributes by land ownership and land cover variables to assess factors that may influence fence specifications (e.g., wire heights) and types (e.g., number of barbed wires). Private land fences had bottom wires that were closer to the ground and top wires higher from the ground when compared to fences on public lands, with sample means at ~22 cm and ~26 cm, and ~115 cm and ~111 cm, respectively. Both bottom wire means were well below recommended heights for ungulates navigating underneath fencing (≥ 46 cm), while top wire means were closer to the 107 cm maximum fence height recommendation. We found that both fence type and land ownership were correlated (χ^2 = 45.52, df = 5, p = 0.001) as well as fence type and land cover type (χ^2 = 140.73, df = 15, p = 0.001). We provide tools for estimating fence locations, and our novel fence type assessment demonstrates an opportunity for updated policy to encourage the adoption of “wildlife-friendlier” fencing standards to facilitate wildlife movement in the western U.S. while supporting rural livelihoods.